Quantifying the effects of chemical and physical properties of skim milk and yogurts using standard methods and a novel rapid detection method - Menard, Sara Lynn (Kansas State University, 2014)
This research sets out to determine how varying factors such as electromagnetic fluid conditioning (EFC) and varying protein and sugar contents can influence yogurt and skim milks overall quality. EFC uses magnets to alter the chemical and physical properties of skim milk in these studies. EFC has many different treatment parameters to optimize before this new processing technology can be industrialized. Treatment parameters include voltage, exposure time, flow rate, and magnetic field direction, as studied in this research. Voltage was altered 10 and 30 V for 2 and 10 minutes. This study showed that at 2 minutes that skim milk was not altered, but at both voltages at 10 minutes some changes occurred to surface tension and color properties (L* and a* values) of skim milk. For both voltages at 10 minutes, it was always the negative direction that experienced the most changes. A separate EFC experiment was done that set out to determine if pretreating skim milk with EFC, would have an effect on yogurt’s quality post fermentation throughout storage. Results indicated that EFC does alter the yogurt’s properties, but not in a desirable manner. Results were undesirable changes to the product’s firmness and syneresis when compared to the control sample. Dielectric spectroscopy is a rapid method to determine if varying protein and sugar contents has compromised yogurt’s quality. In the dielectric spectroscopy study, this research wanted to determine if varying protein and sugar contents influenced dielectric properties enough to where a model could be developed to predict yogurt’s firmness. Both of these methods, EFC and dielectric spectroscopy, are novel technologies to the dairy industry where, both have been very minimally tested on yogurt. This research proved to be a stepping stone to open further doors to research in these areas due to results indicating changes but not pin-pointing exactly what is going on due to these technologies.
Keywords: Yogurt; Electromagnetic fluid conditioning; Dielectric spectroscopy; Quality; Skim milk; Food Science (0359)